Comparison of exfoliative pap stain and AgNOR counts of the tongue in smokers and nonsmokers - Fontes, Patrícia Campos [UNESP]; Corrêa, Gustavo Henrique Marques [UNESP]; Issa, Jaqueline Scholz; Brandão, Adriana Aigotti Haberbeck [UNESP]; Almeida, Janete Dias [UNESP] (Springer Nature, 2008)
Objective To compare exfoliative cytology from the oral mucosa of smokers and nonsmokers, with emphasis on proliferative activity. Methods Exfoliative cytology specimens were obtained from clinical normal mucosa from the lateral border of the tongue in 30 nonsmokers and 30 smokers ranging in age from 40 to 70 years of age, who were seen at the Heart Institute's Patient Center and the Smoking Cessation Program of the University Hospital, University of São Paulo Medical School (InCor-HCFMUSP). The cytologic specimens were evaluated by Papanicolaou staining and AgNOR quantification in order to evaluate the presence of cytological alterations suggestive of inflammation, dysplasia, keratinization, and proliferative activity of epithelial cells. Results Only Papanicolaou Class I and Class II smears were observed. Inflammatory alterations were found in 90% of smokers and in 87% of nonsmokers. The number of AgNORs/nucleus differed significantly between smokers and nonsmokers (3.372 ± 0.375 versus 2.732 ± 0.236). Conclusions Within the limitations of this research, the results indicate higher proliferative activity in smoking patients compared to nonsmoking patients, even in the absence of clinical lesions. © The Author(s) 2008.
Keywords: Cytodiagnosis; Disease prevention; Nucleolar organizer region; Oral mucosa; Smoking; cell nucleus antigen; nucleolar organizer region associated proteins; adult; aged; cell proliferation; chemistry; chromosome NOR; comparative study; cytodiagnosis; drug effect; human; male; metabolism; methodology; middle aged; mouth mucosa; pathology; reproducibility; silver staining; smoking; staining; tongue disease; Adult; Aged; Antigens, Nuclear; Cell Proliferation; Humans; Male; Middle Aged; Mouth Mucosa; Nucleolus Organizer Region; Reproducibility of Results; Silver Staining; Staining and Labeling; Tongue Diseases